Answer:
Equation 1 x=-16
Equation 2 m=-3
Step-by-step explanation:
Equation 1
3x-x=-24-6
2x=-32
x=-32/2
x=-16
Equation 2
-2m=16-10
-2m=6
m=6/-2
m=-3
Answer:
c
Step-by-step explanation:
Two sum of any two side lengths of a triangle will always be greater than the length of the remaining side
a doesn't work because 8+12=20 and 20 is not greater than 20
b doesn't work because 4+5=9 and 9<10
d doesn't work because 6+6=12 and 12 is not greater than 12
c is the only option where you can take any two sides, add them, and the sum will be greater than the remaining side.
For example, for c,
6+8=14, and 14>10
8+10=18, and 18>6
10+6=16, and 16>8
10g^3 - 8g^2 + 5g - 14 + 10g^2 + 12g
its just a matter of combining like terms
10g^3 + 2g^2 + 17g - 14
So if you're asked to graph a function and its inverse, all you have to do is graph the function and then switch all x and y values in each point to graph the inverse. Just look at all those values switching places from the f(x) function to its inverse g(x) (and back again), reflected over the line y = x.
Answer:
B.
Why?
Step-by-step explanation:
"Jessica's teacher asked her to create a "histogram" representing students and cell phone use."
the hint histogram means the history or record of
HOPE IT HELPS
(FROM CROSS)